Carbohydrate Composition of Amphiphilic Macromolecules Influences Physicochemical Properties and Binding to Atherogenic Scavenger Receptor A - Hehir, Sarah (2012)
Amphiphilic macromolecules (AMs) based on carbohydrate domains functionalized with poly(ethylene glycol) can inhibit the uptake of oxidized low density lipoprotein (oxLDL) mediated by scavenger receptor A (SR-A) and counteract foam cell formation, the characteristic “atherosclerotic” phenotype. A series of AMs were prepared by altering the carbohydrate chemistry to evaluate the influence of backbone architecture on the physicochemical and biological properties. Upon evaluating the degree of polymer-based inhibition of oxLDL uptake in human embryonic kidney cells expressing SR-A, two AMs (2a and 2c) were found to have the most efficacy. Molecular modeling and docking studies show that these same AMs have the most favorable binding energies and most close interactions with the molecular model of SR-A collagen-like domain. Thus, minor changes in the AMs architecture can significantly affect the physicochemical properties and inhibition of oxLDL uptake. These insights can be critical for designing optimal AM-based therapeutics for management of cardiovascular disease.